Pengaruh Self Efficacy dan Kecemasan Matematis terhadap Hasil Belajar Mahasiswa Mata Kuliah Statistika Ekonomi - Sari, Alfizah Ayu Indria; Lutfi, Ahmad (Edumatica : Jurnal Pendidikan Matematika, 2024)
This article aims to explain the effect of self-efficacy and mathematical anxiety on student learning outcomes in economic statistics courses. The research respondents were 50 students of the Economics and Sharia Banking Study Program of STES Manna Wa Salwa who had taken the Economic Statistics course. The instruments used in this study were tests and non-tests. Tests are used to measure student economic statistics learning outcomes. While non-tests in the form of self-efficacy questionnaires and mathematical anxiety questionnaires have as many as 20 statement items. Data collection in the form of tests and questionnaires was carried out after the last meeting of the economic statistics lecture. Data analysis using multiple linear regression tests. The results found a significant influence between self-efficacy on student learning outcomes, there is no significant influence between math anxiety on student learning outcomes, and there is a significant influence between self-efficacy and math anxiety together on student learning achievement by 22.7%. Based on the results of the study, we conclude that self-efficacy has a relationship with mathematical anxiety, besides that it is found that students with high mathematical anxiety have high learning outcomes in economic statistics.